Problematics of Implementation and Accountability of State Finance - Fakhrurraji, Ahmad (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The purpose of this study is to determine the problems of implementation and accountability of state finances. This study is a qualitative study with a case study approach. The research method uses an observation method by conducting interviews with informants as primary data and documentation as secondary data. The research site is located in a Government Agency. The informants in this study are budget managers at Government Agencies. The results of the study indicate that there are problems in the implementation and accountability of state finances at Government Agencies. Solution strategies are presented in this study to overcome these problems.